Development and Evaluation of a Tissue-Engineered Fibrin-based Canine Mitral Valve Three-dimensional Cell Culture System. (April 2018) - Liu, M.-M.; Flanagan, T.C.; Jockenhovel, S.; Black, A.; Lu, C.-C.; French, A.T.; Argyle, D.J.; Corcoran, B.M.
Summary: Myxomatous mitral valve disease is the most common cardiac disease of the dog, but examination of the associated cellular and molecular events has relied on the use of cadaveric valve tissue, in which functional studies cannot be undertaken. The aim of this study was to develop a three-dimensional (3D) cell co-culture model as an experimental platform to examine disease pathogenesis. Mitral valve interstitial (VIC) and endothelial (VEC) cells were cultured from normal and diseased canine (VIC only) valves. VICs were embedded in a fibrin-based hydrogel matrix and one surface was lined with VECs. The 3D static cultures (constructs) were examined qualitatively and semiquantitatively by light microscopy, immunofluorescence microscopy and protein immunoblotting. Some constructs were manipulated and the endothelium damaged, and the response examined. The construct gross morphology and histology demonstrated native tissue-like features and comparable expression patterns of cellular (α-smooth muscle actin [SMA] and embryonic smooth muscle myosin heavy chain [SMemb]) and extracellular matrix associated markers (matrix metalloproteinase [MMP]-1 and MMP-3), reminiscent of diseased valves. There were no differences between constructs containing normal valve VICs and VECs (type 1) and those containing diseased valve VICs and normal valve VECs (type 2). Mechanical manipulation and endothelial damage (type 3) tended to decrease α-SMA and SMemb expression, suggesting reversal of VIC activation, but with retention of SMemb + cells adjacent to the wounded endothelium consistent with response to injury. Fibrin-based 3D mitral valve constructs can be produced using primary cell cultures derived from canine mitral valves, and show a phenotype reminiscent of diseased valves. The constructs demonstrate a response to endothelial damage indicating their utility as experimental platforms.